ПЕРЕНАПРУГИ В ЕЛЕКТРИЧНИХ МЕРЕЖАХ ВЛАСНИХ ПОТРЕБ ЕЛЕКТРОСТАНЦІЙ, ЩО ВИНИКАЮТЬ ПІД ЧАС КОМУТАЦІЙ ВАКУУМНИМИ ВИМИКАЧАМИ, ТА ЇХ ОБМЕЖЕННЯ - Равлик, Н.О.; Равлик, О.М.; Сегеда, М.С. (Інститут електродинаміки НАН України, Київ, 2019)
A mathematical model of the electrical network of own needs of power stations unit based on an asynchronous load and switching properties of the vacuum circuit breakers has been developed. Using computer simulation in a specialized digital complex "REC" investigated surge during switches of vacuum circuit breakers in the normal and emergency modes motors of own needs of power stations. References 10, figures 5.